Methodology for the remote transfer of GPS receiver station data through a GSM network - Salsabeel E. Othman (Elsevier, 2021)
Coastline alterations severely impact the socio-economic conditions of populations living in coastal regions. Climate changes, together with land subsidence considerations, have increased recently according to high-accuracy fixed tide gauges and land subsidence sensors. In addition, networks of measurement devices are spread throughout the oceans, seas, and coastal areas to capture ongoing changes and to predict future impacts. However, some of these devices still require the in-situ extraction of data for postprocessing. This increases the cost, wastes time, and increases the probability of human errors leading to inaccurate results. This study presents a developed approach to remotely access the Trimble NetR9 GPS receiver device that is fixed at the Coastal Research Institute station in the city of Rosetta in Egypt. This will ease the remote retrieval of the station data for its processing and interpretation.